2007
DOI: 10.5005/jcdp-8-1-68
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of Self-Reported Oral Hygiene Practices Among Medical and Engineering University Students with Access to Health-promotive Dental Care

Abstract: Aim:This study was conducted to test the null hypothesis that no difference exists in the oral hygiene knowledge and practices of university students in different courses when they have equal opportunity to access health-promotive dental care. Methods and Materials:The study was conducted using 120 students each from the medical and engineering colleges at the University of Manipal Academy of Higher Education who had easy access to the dental college within the campus which provides health-promotive dental car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
4
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 5 publications
6
36
4
5
Order By: Relevance
“…Similar results were reported by Doshi et al . [22] who reported that dental and medical students have better attitudes toward oral health behavior than their counterparts in other faculties. This similarity may be explained by the nature of the clinical curriculum of the Faculty of Medicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were reported by Doshi et al . [22] who reported that dental and medical students have better attitudes toward oral health behavior than their counterparts in other faculties. This similarity may be explained by the nature of the clinical curriculum of the Faculty of Medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also reported higher HU-DBI scores for female students than male students, confirming that there is a significant relationship between gender and oral health attitude and behavior. [162122] Al-Ansari and Honkala[31] have found that female students practiced better oral hygiene and possessed more knowledge about oral health maintenance than male students. Al-Shammari et al .…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Doshi et al. (1), there was no significant difference in the usage of fluoridated tooth paste usage, tongue cleaning, mouth rinsing after meals and dental service utilization among the medical and engineering students, but the brushing after every meal and the dental floss use were significantly higher among the medical students than among the engineering students ( P < 0.001) for both.…”
Section: Discussionmentioning
confidence: 83%
“…Any nation can progress rapidly when its people are healthy and lead a productive life. Since the adoption of WHO definition of health (1948), resources around the world have been trying to raise the critical consciousness of people to effect a change from existing disease‐centric, pain‐relieving notion of health care to promoting a health‐centric and well‐being concept (1).…”
Section: Introductionmentioning
confidence: 99%
“…Of concern was that the high rate of overweight and obesity (26.8% and 10.7%, respectively), low rate of brushing teeth at least twice a day (28.6%),) annual dental check-up (25.8%), habitual seatbelt use (23%), poor dietary patterns (79% ate less than the recommended 5 servings of fruits and vegetables a day and 68.5% did not avoid eating fat and cholesterol), and a large proportion (30.6%) who slept on average only 6 or less hours in a day. Other studies among Indian university students also found poor dental practices, i.e., 32% went for a dental check up at least every 6 months and 44.1% of medical students and 39.1% of engineering students brushed their teeth twice daily (63). These findings suggest the need to focus attention on university students as a target group for health education campaigns to maintain their BMI within the normal range, to improve their dietary behaviors, to improve dental care and sleep duration, to increase seatbelt use, and to reduce substance use.…”
Section: Discussionmentioning
confidence: 93%